Real-life cost savings and capacity improvements on implementation of the new BSG post-polypectomy surveillance guideline. Issue 1 (2020) - Shandro, Benjamin; Chang, Vincent; Mathur, Jai; O'Neill, Parker; Groves, Christopher; Sadler, Gareth
No abstract available